Coming to Terms with the Communist Past in Romania: An Analysis of the Political and Media Discourse Concerning the Tismăneanu Report - Hogea, Alina (Studies of Transition States and Societies, 2010)
This paper looks at the public debates about the communist past, as triggered by the final report on the communist dictatorship in Romania (the Tismăneanu report) and its presidential endorsement in December 2006. The paper employs narrative and discourse analysis to examine the political reactions to the official condemnation of communism, as well as its reflection in several Romanian newspapers. The Tismăneanu report was meant to be a ‘redressive ritual’ that would provide closure to a traumatic past by retrospectively denouncing the meaning of communism, but instead it generated more public debates and political turmoil. This indicates that the contorted path taken by Romania to confront its communist past is not a finished process yet, but rather represents a dynamic field in which social actors are fighting over which events and actors in the past should be collectively remembered, and especially how they have to be represented in the collective memory of post-communist Romania.